2019
DOI: 10.1158/1078-0432.ccr-18-3223
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glutamine Metabolism and Redox State for Leukemia Therapy

Abstract: Purpose: Acute myeloid leukemia (AML) is a hematologic malignancy characterized by the accumulation of immature myeloid precursor cells. AML is poorly responsive to conventional chemotherapy and a diagnosis of AML is usually fatal. More effective and less toxic forms of therapy are desperately needed. AML cells are known to be highly dependent on the amino acid glutamine for their survival. These studies were directed at determining the effects of glutaminase inhibition on metabolism in AML and identifying gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 45 publications
0
81
1
Order By: Relevance
“…Of note, since the cytotoxicity of conventional anti-cancer therapies largely relies on efficient ROS accumulation, the augmented antioxidant capacity of cancer cells constitutes a key determinant of therapy-resistance [286][287][288]. At the same time, given the strong dependency of malignant cells to their antioxidant systems, interfering with their redox control can induce OS-dependent cell death [289]. Since the NRF2 signaling plays a key role in tumorigenesis, malignant progression [290][291][292] and drug sensitivity [293][294][295], this transcription factor has emerged as a promising therapeutic target [16,282,[296][297][298].…”
Section: Strategies To Negatively Modulate Nrf2 Signaling/pathwaymentioning
confidence: 99%
“…Of note, since the cytotoxicity of conventional anti-cancer therapies largely relies on efficient ROS accumulation, the augmented antioxidant capacity of cancer cells constitutes a key determinant of therapy-resistance [286][287][288]. At the same time, given the strong dependency of malignant cells to their antioxidant systems, interfering with their redox control can induce OS-dependent cell death [289]. Since the NRF2 signaling plays a key role in tumorigenesis, malignant progression [290][291][292] and drug sensitivity [293][294][295], this transcription factor has emerged as a promising therapeutic target [16,282,[296][297][298].…”
Section: Strategies To Negatively Modulate Nrf2 Signaling/pathwaymentioning
confidence: 99%
“…This important role of glutaminase in glutamine metabolism makes it a valuable target for cancer therapy. The application of glutaminase inhibitors attenuates the glutamine to glutamate conversion, elevates intracellular ROS level and impairs antioxidant GSH production in cancer cells (15,115,116). Furthermore, the combination of glutaminase inhibitors with chemotherapy agents also increased sensitivity of cancer cells to chemotherapy in pancreatic cancer and ovarian cancer (59, 117, 118).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Glutamine is an important metabolite for the synthesis of the tripeptide glutathione, the prime ROS scavenger (Figure 4). The utilization of glutamine has shown to be essential for redox control in AML [103]. Gregory et al (2018) showed that CB-839 inhibited glutathione production, that this provoked accumulation of mitochondrial ROS in multiple AML types, and subsequently apoptotic cell death (Figure 5).…”
Section: Amino Acid Metabolism In Amlmentioning
confidence: 99%